Evaluasi Diri Keluarga dalam Merawat Anggota Keluarga dengan Stroke - Jesika Enggelina Humau; Masta Haro (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the description of family self-evaluation in caring for family members with stroke and to find out the most dominant and less dominant categories of family self-evaluation from 8 categories: understanding of self-care, benefits of self-care bathing, dressing, eating, elimination, mobilization and hygiene. The design in this study is a quantitative descriptive analysis. The results showed that the average family self-evaluation in caring for family members with stroke was good, namely 82.22%-100%. In contrast, the most dominant category of the eight categories above was the benefits of self-care and elimination with a percentage value of 100%. The less dominant category is dressing, with a percentage value of 82.22%. Although this category has a lower number than the other categories, it is still in the good category. In conclusion, family self-evaluation in caring for family members with stroke is in the good category. Keywords: Family Self Evaluation, Self Care, Stroke